Prevention of diabetic eye disease: the commonest cause of blindness in individuals younger than 65 years - Patrizio Tatti (Dove Medical Press, 2010)
Patrizio Tatti1, Patrizia Di Mauro1, Leonardo Masselli1, Adriano Longobardi2, Annabel Barber31Diabetes and Endocrinology Department, 2UOS Eye Surgery, Ospedale S Giuseppe, ASL RMH, Rome, Italy; 3University of Nevada School of Medicine, Las Vegas, NV, USAAbstract: There has been a considerable advancement in the treatment of diabetes and understanding of the biochemical mechanisms underlying diabetic complications in the last 20 years. However, this advancement has not translated into a consistent reduction in diabetic retinopathy, one of the most frightening complications of diabetes mellitus. It is probable that greater attention to preventive intervention will help reduce the damage load in the next future, and that several drugs for the treatment of more advanced stages of diabetic retinopathy will become available. Competent strategies targeting prevention based on screening programs should be proposed to reduce the burden and to improve the clinical outcome of this devastating diabetes complication.Keywords: blindness, diabetes, eye disease, prevention